Employer branding and employee value proposition: The key success of startup companies in attracting potential employee candidates - Rizqi Ariyanto; Kustini Kustini (Annals of Human Resource Management Research, 2021)
Purpose: This study aims to analyze employer branding and employee value proposition on employer attractiveness in potential employee candidates of Startup Campuspedia Indonesia. Research methodology: This study uses quantitative research methods that are processed using Smart PLS software. The sampling technique used is proportional random sampling with a total of 51 samples. Results: The results show that employer branding and employee value proposition have a positive and significant impact on employer attractiveness at Startup Campuspedia Indonesia. Limitations: The limitation of this study is that it only uses one startup company in the field of education as the object of research and has not used several companies with different backgrounds. Contribution: The results of this study can be useful for Human Capital in the company's recruitment process in the next period as an effort to increase the interest of prospective employees to work in the company.